Utility and Reliability of Reporting Information - Directions of Changes - Kaczmarczyk , Angelika (Studia Oeconomica Posnaniensia, 2016)
The accounting system is the starting point for reporting information. Despite certain expectations of the users of the reporting information, this information should have attributes. The purpose of this article is an attempt to answer the question of whether it is possible to ensure the usefulness of information reporting for all of its customers and whether the individual quality characteristics are not mutually exclusive.